Framing Pemberitaan Kasus Korupsi Impor Gula Tom Lembong pada Media Online Tempo.co - Mustiawan; Titin Setiawati; Wafda Izzati Hasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the framing of news coverage on the sugar import corruption case involving Tom Lembong on Tempo.co online media. The case attracted public attention because it involved a former Minister of Trade for the 2015-2016 period with allegations of state losses reaching Rp 400 billion related to the issuance of raw crystal sugar import permits. The research aims to analyze how Tempo.co framed the news coverage of the case through the perspectives it built. The research method uses a qualitative descriptive approach with Robert N. Entman's framing analysis model consisting of four elements: Problem Definition, Diagnosis of Causes, Moral Judgment, and Treatment Recommendation. Research data was obtained from 10 online news articles from Tempo.co during the period of October 29 to November 15, 2024. The results show that Tempo.co tends to take a critical position towards the determination of suspects by the Attorney General's Office by questioning the political motives behind the case. The media framed the case as a more complex issue by highlighting the need for investigation of all trade ministers from the 2015-2023 period, emphasizing the importance of a fair and professional legal process, and encouraging transparency in handling the case. Tempo.co's framing reflects the media's role as a democratic watchdog that criticizes government actions and public institutions to provide a more comprehensive view to society.